DAMPAK KEBIJAKAN DANA ALOKASI KHUSUS PERTANIAN TERHADAP PERTUMBUHAN EKONOMI SEKTOR PERTANIAN DI INDONESIA - Mukiwihando, Rynalto (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2020)
one of the main economic policies of Indonesia government is to boost productivity in agriculture sector. This sector plays a vital role for sustainable development in the country, by providing food security to the people. Unlike previous studies, this paper investigates the impact of special allocated fund (DAK) in agriculture to economic growth in respected sector. Utilizing 38 municipals in East Java as the biggest rice producer province in Indonesia, this study arguea that there is a positive effect of DAK in agriculture to GDP Growth in agriculture. This sectoral research implies to maintain this specific grant scheme implementation in this particularly in primary sector fto create sustainable development in Indonesia.